HHV‐6 encephalitis may complicate the early phase after allogeneic hematopoietic stem cell transplantation: Detection by qualitative multiplex PCR and subsequent quantitative real‐time PCR. Issue 2 (20th August 2015) - Inazawa, Natsuko; Hori, Tsukasa; Yamamoto, Masaki; Hatakeyama, Naoki; Yoto, Yuko; Nojima, Masanori; Yasui, Hiroshi; Suzuki, Nobuhiro; Shimizu, Norio; Tsutsumi, Hiroyuki
Abstract : Viral reactivation following hematopoietic stem cell transplantation (HSCT) can cause various complications especially viral encephalitis. In this prospective study, we investigated the correlation of post‐HSCT viral reactivation in blood with CNS dysfunction. We employed a multiplex PCR that detects 13 kinds of viruses as a first‐line screening test and real‐time PCR for subsequent quantitative evaluation. Five hundred ninety‐one whole blood samples were collected from 105 patients from before until 42 days after HSCT. Seven patients developed CNS dysfunction such as altered consciousness. In six of the seven, the multiplex PCR test detected HHV‐6 DNA in at least one sample. In contrast, DNA from other viruses, such as CMV, EBV, HHV‐7, adenovirus, and HBV was never detected in any of the seven patients throughout the study period. Quantitative measurement of whole blood HHV‐6 DNA levels demonstrated four of the six HHV‐6 DNA loads were elevated at successive time points during the CNS dysfunction. In addition, the virus DNA peaks were temporally associated with the development of CNS dysfunction. CSF was tested in two of the four patients and high HHV‐6 DNA levels comparable to those in whole blood were confirmed in both. These four patients were, thus, suspected to have developed HHV‐6 encephalitis, a rate of 3.8% in the study population. Our results suggest that early diagnosis of probable HHV‐6 encephalitis can be improved by confirming high HHV‐6 DNA load in blood. J. Med. Virol. 88:319–323, 2016 . © 2015 Wiley Periodicals, Inc.